2023
DOI: 10.1007/s00438-023-02008-2
|View full text |Cite
|
Sign up to set email alerts
|

Novel mutation in LRP5 gene cause rare osteosclerosis: cases studies and literature review

Abstract: To study the effects of low-density lipoprotein receptor-related protein 5 (LRP5) gene mutations on bone, and to open up our view of LRP5 and Wnt pathways on bone mass regulation. Three patients with increased bone mineral density or thickened bone cortex were included, who were 30-year-old, 22-year-old and 50-year-old men, respectively. The latter two patients were son and father of a same family. The characteristics of bone X-rays were evaluated in detail. Bone turnover markers were detected, such as procoll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Since then, a body of literature has emerged describing patients with the LRP5 variant-related high bone mass trait (Figure 5). A 2023 case report and review article by Zhao et al summarized the clinical characteristics reported for 113 patients with LRP5-activating variants (Table 1) [52]. Among the 43 cases they examined for which lumbar spine BMD data were available, 40 patients (93%) had Z-scores greater than 2.5, indicating that they had BMD scores at the 99th percentile compared to age-and sex-matched norms [52].…”
Section: High Bone Mass Phenotypes Related To Lrp5mentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, a body of literature has emerged describing patients with the LRP5 variant-related high bone mass trait (Figure 5). A 2023 case report and review article by Zhao et al summarized the clinical characteristics reported for 113 patients with LRP5-activating variants (Table 1) [52]. Among the 43 cases they examined for which lumbar spine BMD data were available, 40 patients (93%) had Z-scores greater than 2.5, indicating that they had BMD scores at the 99th percentile compared to age-and sex-matched norms [52].…”
Section: High Bone Mass Phenotypes Related To Lrp5mentioning
confidence: 99%
“…A 2023 case report and review article by Zhao et al summarized the clinical characteristics reported for 113 patients with LRP5-activating variants (Table 1) [52]. Among the 43 cases they examined for which lumbar spine BMD data were available, 40 patients (93%) had Z-scores greater than 2.5, indicating that they had BMD scores at the 99th percentile compared to age-and sex-matched norms [52]. Furthermore, 51 out of 57 cases (90%) that were assessed for mandible enlargement were found to have this phenotype [52], which is consistent with the previous work conducted by Gregson and Duncan who reviewed the body of literature on patients with LRP5 variant-related high bone mass phenotypes and also found this to be a prominent characteristic [53].…”
Section: High Bone Mass Phenotypes Related To Lrp5mentioning
confidence: 99%
“…On the other hand, we included papers written in 2002 or later only if LRP5 gene analysis was performed. According to these parameters, we included 155 patients (74 males and 81 females) described in 32 case reports published in the literature [ 4 – 8 , 16 , 18 22 , 24 , 25 , 27 – 42 , 42 44 ], including our patient herein described. Sixty-four patients (41%) out of these 155 underwent genetic analysis of the LRP5 gene and can be considered as being affected by LRP5 HBM.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Notably, one study recently reported the first missense mutation (R1414S) affecting a domain other than the first β-propeller domain of LRP5. The R1414S is in exon 20, which codes for the cytoplasmic domain of the LRP5 co-receptor protein; this affects the downstream release of β-catenin and thus can also determine HBM [ 42 ]. The different LRP5 mutations and all the reports in which they were detected are listed in Table 2 .…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation